2021
DOI: 10.22225/jraw.2.1.2929.35-40
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Current Ratio, Debt to Equity Ratio, Return on Equity Terhadap Earning Per Share pada Perusahaan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia 2014-2018

Abstract: Penelitian ini bertujuan untuk menganalisis Pengaruh Current ratio, Debt to equity Ratio, Return on Equity Terhadap Earning per Share pada Perusahaan Sub Sektor Batu Bara yang Terdaftar Di Bursa Efek Indonesia 2014-2018. Data penelitian dikumpulkan melalui analisis data laporan posisi keuangan dan laporan laba rugi perusahaan. Jenis data yang digunakan yaitu data kualitatif. Jumlah populasi dalam penelitian ini sebanyak 21 perusahaan yang ditentukan dengan metode purposive sampling. Teknik analisis data memaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…So it can be concluded that t count > t table (2.446 > 1.98238) and significance < 0.05 (0.016 < 0.05) which means Ha is accepted or the Current Ratio variable has a positive effect on Earnings Per Share. The results of this study are in line with the results of previous studies conducted by (Pouraghajan et al 2013), (Jufrizen, 2019) and (Susilawati, 2014), (Van Rate, 2014) and (Faruq, 2021) which stated that the existence of The influence of the Current Ratio on dividend policy is measured using the Earnings Per Share indicator.…”
Section: Effect Of Debt To Equity Ratio On Firm Valuesupporting
confidence: 90%
See 1 more Smart Citation
“…So it can be concluded that t count > t table (2.446 > 1.98238) and significance < 0.05 (0.016 < 0.05) which means Ha is accepted or the Current Ratio variable has a positive effect on Earnings Per Share. The results of this study are in line with the results of previous studies conducted by (Pouraghajan et al 2013), (Jufrizen, 2019) and (Susilawati, 2014), (Van Rate, 2014) and (Faruq, 2021) which stated that the existence of The influence of the Current Ratio on dividend policy is measured using the Earnings Per Share indicator.…”
Section: Effect Of Debt To Equity Ratio On Firm Valuesupporting
confidence: 90%
“…This is reinforced by the results of previous research conducted by Taani (2011), Pouraghajan et al (2013), Jufrizen, (2019), Susilawati, (2014 and Van Rate (2014), which state that there is a significant influence between the Debt to Equity Ratio on dividend policy which is measured using the Earnings Per Share indicator. However, it is inversely proportional to the results of previous research conducted by Faruq, (2021) which states that the Debt to Equity Ratio has a negative and significant effect on dividend policy which is measured using the Earning Per Share indicator. Thus, the following hypothesis can be formulated:…”
Section: Effect Of Debt To Equity Ratio On Dividend Policymentioning
confidence: 92%